Studies on the role of matrix vesicles in bone mineralization: observations from micro to nanoscale - Cruz, Marcos Antonio Eufrásio (2023)
Bone biomineralization is a complex process that involves the deposition of calcium phosphate crystals on collagen fibrils of the extracellular matrix (ECM). Although matrix vesicles (MVs) have been proposed to be responsible for the initial mineral formation, their role and mechanisms are still not fully understood. This thesis aimed to examine the interplay between MVs and forming mineral during bone mineralization at three levels: individual vesicle observation, mineralization at the interface of a membrane-like model, and in vitro mineralization using osteoblasts culture. To investigate the underlying factors that mediate mineralization in vitro, MVs were isolated from embryonic chicken bones, and their contents, as well as their ability to initiate mineral formation, were examined at a single-vesicle level using near-native cryogenic transmission electron microscopy. This approach revealed that MVs preparations contain non-vesicular particles in addition to bilayered vesicles, affecting the outcome of mineralization experiments. Further investigations using comparative purification and mineralization experiments demonstrated that the primary pathway by which MVs trigger mineralization is through their enhanced phosphatase activity, such as alkaline phosphatase, with the direct mineral nucleation from soluble ions being a secondary process driven by their membrane components. To access this secondary effect, surface-induced mineral nucleation was accessed in a biomimetic model using Langmuir monolayers of synthetic (e.g. phosphatidylcholine and phosphatidylserine) as well as native lipids extracted from MVs. Insitu tracking of mineral formation at Langmuir monolayers revealed that phosphatidylserineenriched nanodomains formed at the membrane surface trigger the mineral nucleation by interacting with calcium and phosphate ions. Having established the interplay between MVs and forming mineral both at the single-vesicle level and using a membrane-like model, the role of MVs in controlling ECM mineralization was finally demonstrated in a primary osteoblast culture. Osteoblasts treated with chloroquine, a blocker of autophagy, resulted in defective ECM mineralization. Although mineralization was impaired, as revealed by alizarin red calcium staining, transmission electron microscopy revealed that MVs were still abundantly present throughout the ECM. However, isolation of MVs and characterization of their content demonstrated reduced expression of mineralization-related proteins, with a remarkable decrease in alkaline phosphatase activity. These observations at cell level suggested that ECM mineralization is impaired when MVs are dysfunctional (i.e., reduced phosphatase activity) and that these structures play a predominant role in bone mineralization, being their release controlled in a cell-context-specific manner.In conclusion, the findings presented in this thesis collectively validate the crucial role of MVs in bone mineralization while also providing valuable insights into the complex interplay between vesicles and the mineralization process.